Disclosure of Estimates of Holding Gains and the Assessment of Systematic Risk - Abdel-Khalik, A. Rashad; Mckeown, James C. (Journal of Accounting Research, 1978)
A. Rashad Abdel-Khalik, James C. Mckeown, Disclosure of Estimates of Holding Gains and the Assessment of Systematic Risk, Journal of Accounting Research, Vol. 16, Studies on Changes in General and Specific Prices: Empirical Research and Public Policy Issues (1978), pp. 46-77